Hepatoprotective activity of aerial parts of Otostegia persica against carbon tetrachloride-induced liver damage in rats - Mehdi Akbartabar Toori; Behzad Joodi; Heibatollah Sadeghi; Hossein Sadeghi; Mehrzad Jafari; Mohammad Sharif Talebianpoor; Foad Mehraban; Mostafa Mostafazadeh; Mehdi Ghavamizadeh (Mashhad University of Medical Sciences, 2015)
Objective: To evaluate the hepatoprotective properties of Otostegia persica (O. persica) ethanol extract on carbon tetrachloride-induced liver damage in rats. Materials and Methods: Fifty adult male Wistar rats were randomly divided into five groups. Group I served as normal control and was given only olive oil intraperitoneally (i.p.). Group II, III, IV, and V were administered CCl4 mixed with olive oil 1:1 (1 ml/kg) i.p., twice a week for 8 weeks. Group II was maintained as CCl4-intoxicated control (hepatotoxic group). Group III, IV, and V received O. persica extract at a dose of 40, 80, and 120 mg/kg for 8 weeks every 48 h orally, respectively. Biochemical parameters including aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), total bilirubin (TB), albumin (ALB), total protein (TP), and lipid peroxidation marker (Malonaldialdehyde, (MDA) were determined in serum. After 8 weeks, animals were sacrificed, livers dissected out, and evaluated for histomorphological changes. Results: The administration of CCl4 increased AST, ALT, ALP, TB, and MDA in serum but it decreased TP , and ALB compared with normal control. Treatment with O. persica extract at three doses resulted in decreased enzyme markers, bilirubin levels, and lipid peroxidation marker (MDA) and increased TP and ALB compared with CCl4 group. The results of pathological study also support the hepatoprotective effects which were observed at doses of 80 and 120 mg/kg. Conclusion: The results of the present study indicate that ethanol extract of O. persica may have hepatoprotective effect which is probably due to its antioxidant property.